Knockdown of PagSAP11 Confers Drought Resistance and Promotes Lateral Shoot Growth in Hybrid Poplar (Populus alba × Populus tremula var. glandulosa) - Park, Su Jin; Bae, Eun-Kyung; Choi, Hyunmo; Yoon, Seo-Kyung; Jang, Hyun-A; Choi, Young-Im; Lee, Hyoshin (Frontiers in Plant Science, 2022)
Plants have evolved defense mechanisms to overcome unfavorable climatic conditions. In response to environmental stress, the growth and development of plants are regulated. In this study, we investigated the molecular and physiological characteristics of a novel gene PagSAP11 in hybrid poplar (Populus alba × P. tremula var. glandulosa) under drought stress. PagSAP11, a stress-associated protein (SAP) family gene, encodes a putative protein containing an A20 and AN1 zinc-finger domain at its N- and C-termini, respectively. Knockdown of PagSAP11 transgenic poplars enhanced their tolerance to drought stress compared with wild type plants. Moreover, the RNAi lines showed increased branching of lateral shoots that led to a gain in fresh weight, even when grown in the living modified organism (LMO) field. The expression levels of genes involved in axillary bud outgrowth and cell proliferation were increased in SAP11-Ri transgenic plants, while the expression of genes involved in bud dormancy was decreased. Taken together, these results indicate that PagSAP11 represents a promising candidate gene for engineering trees with improved stress tolerance and growth during unfavorable conditions.